Antihypertensive medications and risk for incident dementia and Alzheimer's disease: a meta-analysis of individual participant data from prospective cohort studies - Ding, Jie; Davis-Plourde, Kendra L; Sedaghat, Sanaz; Tully, Phillip J; Wang, Wanmei; Phillips, Caroline; Pase, Matthew P; Himali, Jayandra J; Gwen Windham, B; Griswold, Michael; Gottesman, Rebecca; Mosley, Thomas H; et al. (Lancet neurology, 2020)
Dementia is a major health concern for which prevention and treatment strategies remain elusive. Lowering high blood pressure with specific antihypertensive medications (AHMs) could reduce the burden of disease. We investigated whether specific AHM classes reduced the risk for dementia. We did a meta-analysis of individual participant data from eligible observational studies published between Jan 1, 1980, and Jan 1, 2019. Cohorts were eligible for inclusion if they prospectively recruited community-dwelling adults; included more than 2000 participants; collected data for dementia events over at least 5 years; had measured blood pressure and verified use of AHMs; included in-person exams, supplemented with additional data, to capture dementia events; and had followed up cases for mortality. We assessed the association of incident dementia and clinical Alzheimer's disease with use of five AHM classes, within strata of baseline high (systolic blood pressure [SBP] ≥140 mm Hg or diastolic blood pressure [DBP] ≥90 mm Hg) and normal (SBP <140 mm Hg and DBP <90 mm Hg) blood pressure. We used a propensity score to control for confounding factors related to the probability of receiving AHM. Study-specific effect estimates were pooled using random-effects meta-analyses. Six prospective community-based studies (n=31 090 well phenotyped dementia-free adults older than 55 years) with median follow-ups across cohorts of 7–22 years were eligible for analysis. There were 3728 incident cases of dementia and 1741 incident Alzheimer's disease diagnoses. In the high blood pressure stratum (n=15 537), those using any AHM had a reduced risk for developing dementia (hazard ratio [HR] 0·88, 95% CI 0·79–0·98; p=0·019) and Alzheimer's disease (HR 0·84, 0·73–0·97; p=0·021) compared with those not using AHM. We did not find any significant differences between one drug class versus all others on risk of dementia. In the normal blood pressure stratum (n=15 553), there was no association between AHM use and incident dementia or Alzheimer's disease. Over a long period of observation, no evidence was found that a specific AHM drug class was more effective than others in lowering risk of dementia. Among people with hypertensive levels of blood pressure, use of any AHM with efficacy to lower blood pressure might reduce the risk for dementia. These findings suggest future clinical guidelines for hypertension management should also consider the beneficial effect of AHM on the risk for dementia. The Alzheimer's Drug Discovery Foundation and the National Institute on Aging Intramural Research Program.